Bacterial lysates: conventional views and a new paradigm - A.L. Zaplatnikov; A.A. Garina; V.I. Svinitskaya; Lepiseva I.V; M.V. Leshik (LCC «Medicine-Inform», 2021)
A.L. Zaplatnikov1, A.A. Girina2, V.I. Svintsitskaya1, I.V. Lepiseva3, M.V. Leshik1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Khanty-Mansi State Medical Academy, Khanty-Mansiysk, Russian Federation 3Children's Republican Hospital, Petrozavodsk, Russian Federation This paper addresses published data on therapeutic, preventive efficacy, and safety of bacterial lysates (BLs) in pediatric practice. Studies on the mechanisms of action of BLs are discussed. Experimental evidence demonstrates that the preventive effect of BLs is maintained even in the high level of bacterial lysis characterized by the presence of only small peptides or even their fragments without antigenic properties. The authors discuss the potential involvement of BLs in the development of trained immunity, whose effects last less time than a conventional epitope-specific adaptive immune memory. The article provides a pathogenic basis for BL use to prevent and manage recurrent respiratory infections and control respiratory allergic diseases as a part of complex treatment. Our data demonstrate a high efficacy of polyvalent mechanical BL to prevent acute and recurrent respiratory infections in children of organized communities, a reduced rate of bacterial complications, and 20 the rate of antibiotic prescription when using BLs. Good tolerability and the lack of adverse and side effects of BLs are emphasized. Keywords: bacterial lysates, asthma, children, immunity, immune prophylaxis, polyvalent mechanical bacterial lysate, respiratory infections, recurrent respiratory infections, trained immunity. For citation: Zaplatnikov A.L., Girina A.A., Svintsitskaya V.I. et al. Bacterial lysates: conventional views and a new paradigm. Russian Journal of Woman and Child Health. 2021;4(3):284-291 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-284-291.